Is leg compression beneficial for alpine skiers? - Sperlich, B.; Born, D.-P.; Swaren, M.; Kilian, Y.; Geesmann, B.; Kohl-Bareis, M.; Holmberg, H. C. (BMC Sports Science, Medicine and Rehabilitation, 2013)
This study examined the effects of different levels of compression (0, 20 and 40 mmHg) produced by leg garments on selected psycho-physiological measures of performance while exposed to passive vibration (60 Hz, amplitude 4-6 mm) and performing 3-min of alpine skiing tuck position. Methods: Prior to, during and following the experiment the electromygraphic (EMG) activity of different muscles, cardio-respiratory data, changes in total hemoglobin, tissue oxygenation and oscillatory movement of m. vastus lateralis, blood lactate and perceptual data of 12 highly trained alpine skiers were recorded. Maximal isometric knee extension and flexion strength, balance, and jumping performance were assessed before and after the experiment. Results: The knee angle (-10°) and oscillatory movement (-20-25.5%) were lower with compression (P<0.05 in all cases). The EMG activities of the tibialis anterior (20.2-28.9%), gastrocnemius medialis (4.9-15.1%), rectus femoris (9.6-23.5%), and vastus medialis (13.1-13.7%) muscles were all elevated by compression (P<0.05 in all cases). Total hemoglobin was maintained during the 3-min period of simulated skiing with 20 or 40 mmHg compression, but the tissue saturation index was lower (P<0.05) than with no compression. No differences in respiratory parameters, heart rate or blood lactate concentration were observed with or maximal isometric knee extension and flexion strength, balance, and jumping performance following simulated skiing for 3 min in the downhill tuck position were the same as in the absence of compression. Conclusions: These findings demonstrate that with leg compression, alpine skiers could maintain a deeper tuck position with less perceived exertion and greater deoxygenation of the vastus lateralis muscle, with no differences in whole-body oxygen consumption or blood lactate concentration. These changes occurred without compromising maximal leg strength, jumping performance or balance. Accordingly, our results indicate that the use of lower leg compression in the range of 20-40 mmHg may improve alpine skiing performance by allowing a deeper tuck position and lowering perceived exertion.